CTNI-17. A PHASE 1 WITH DOSE EXPANSION/PHASE 2 STUDY OF SELINEXOR IN COMBINATION WITH STANDARD OF CARE THERAPY FOR NEWLY DIAGNOSED OR RECURRENT GLIOBLASTOMA. (12th November 2021) - Odia, Yazmin; Wen, Patrick; Mehta, Minesh; Colman, Howard; Dunbar, Erin; Butowski, Nicholas; Harrison, Rebecca; Schulder, Michael; Boockvar, John; Chow, Frances; Kumthekar, Priya; Mason, Warren; et al.
Abstract: BACKGROUND: Glioblastoma (GBM) is the most common and aggressive primary brain tumor with median overall survival of 15 months and 5-7 months for patients with newly diagnosed or recurrent disease (nGBM or rGBM), respectively. Selinexor is a first-in-class, oral, selective inhibitor of nuclear export which blocks exportin 1 (XPO1), forcing the nuclear retention and reactivation of tumor suppressor proteins, ultimately causing cancer cell death. Increased XPO1 expression in gliomas is associated with higher pathological grade and poorer prognosis. Consistent with these data, selinexor inhibited tumor growth and prolonged survival in an animal model of GBM. Importantly, selinexor showed encouraging intra-tumoral penetration and single-agent efficacy in rGBM (KING study). The current trial tests the hypothesis that adding selinexor to standard therapy will improve clinical outcomes for patients with nGBM or rGBM. METHODS: To facilitate the successful development of new therapies, consensus recommendations are to use biomarker enrichment and flexible design that allows expansion of promising cohorts. Accordingly, this phase 1a dose finding study is followed by a phase 1b dose expansion (and ultimately by a 1:1 randomized phase 2 efficacy exploration trial) to independently evaluate: radiation + selinexor in nGBM with unmethylated MGMT promoter (Arm A), radiation + temozolomide + selinexor for nGBM with methylated MGMT promoter (Arm B), and lomustine + selinexor in rGBM (Arm C). Bevacizumab or TTField + selinexor in rGBM (Arms D & E, respectively) are being considered. The Phase 1a primary endpoint is maximum tolerated dose/recommended phase 2 dose. The phase 1b primary endpoint is PFS at 3 months against historic controls. The phase 1b dose expansion is included to evaluate preliminary efficacy before launching into a randomized phase 2 trial. Patient quality of life during the trial will be objectively measured using digital devices (e.g. smartwatch/customized smartphone app). We are currently enrolling patients nationwide. Clinical Trial Registration number: NCT04421378.